A study of language teacher identity negotiations of ecuadorian english teachers - Kandappankattil Narayanan, Vinu (2022)
In the changing social, political, and cultural environment of a language classroom, a Language Teachers’ professional identity plays a significant role. In the postmodern sense of the word, one’s identity is actively under construction. This fragmented, multiple, expansive identity determines one’s sense of self. Beyond professional and pedagogical knowledge that is expected of teachers, this multidimensional realm of teacher training receives little attention (Tsui, 2007). Language teachers and learners cannot remove themselves from the reality that they are engaged in the process of negotiating their identities. This process is made further complex because of the intricacy of the relationship between language and culture. English as Foreign/Second Language teachers and learners additionally struggle with the coloniality of the language and the globality of its position. These factors loom in the proscenium of an English class, actively interacting with every communicative activity conducted within. Cultural globalization, identity formation and English language education, and their interconnectedness cannot be brushed aside (Kumaravadivelu, 2008, 2012). In this research, the identity negotiation of an Ecuadorian language teacher is viewed through the looking glass of the native-nonnative dichotomy that exists in every decision and methodology in an English class. It then studies about how teachers reflect, reify, resist, and reinvent their subjectivities. In the conclusion, the implications of the fragmented and complex identities are analyzed and possible applications in teacher education is explored.